Pembelajaran Metode Dirosa di Desa Majannang Kabupaten Gowa - Hendra Wijaya; Nurhidayah (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
Koran Education for Adult (Dirosa) was one well-known program of students of Community Service Program (KKN) of STIBA Makassar held in Majannang village, Parigi District, Gowa Regency, South Sulawesi Province. The objectives of this program were; (1) To increase enthusiasm in learning and teaching the Koran for teenagers and adults, (2) To provide teenagers and adults learning for reading Koran so that they can read it according to the knowledge of recitation. (3) To provide additional knowledge of the basics of Islam for teenagers and adults. The implementation of Dirosa program in Majannang village was of 7 study groups, with details: 2 groups of men, 2 groups of women, and 3 groups of young men. The number of participants initially was 59 people and has succeeded in resulting as many as 23 alumni who consistently attended 20 meetings. Most participants before participating Dirosa program did not read the Koran fluently, neither do they understand the knowledge of recitation, and there were among them who were illiterate in the Koran, after participating in Dirosa program they became proficient in reading the Koran according to the principles of recitation, people of Majannang village also received additional knowledge about Islamic insights, especially those which are related to Islamic practices of worship and morality.